The relationship among acceleration, deceleration and changes of direction in repeated small sided games - Konefal, M.; Chmura, J.; Zacharko, M.; Zajac, T.; Chmura, P. (Journal of Human Kinetics, 2022)
The change of direction (COD) ability is perhaps the most significant fitness component in team sport games. One of the best ways to develop COD as well as other components of the game in soccer is the regular inclusion of small sided games (SSGs) in the training process. Therefore, the aim of this research was to determine changes in physiological and kinematic variables in repeated SSGs in youth soccer players. Additionally, we investigated the relationship between selected IMA variables such as acceleration, deceleration and changes of direction. Participants included sixteen U17 soccer players from a 2 nd league professional team with a high aerobic capacity. The study design involved six 3-min 4 × 4 SSGs with goalkeepers and with a 3-min rest interval between games, during two training sessions played on a field of 25 x 35 m. The results showed that the intervention protocol consisting of repeated SSGs generated an intensity below the anaerobic threshold. This allowed for the maintenance of all variables (Heart Rate, Total Distance Covered, Velocity, Acceleration, Deceleration, Change of Direction) at a similar level throughout the subsequent six SSGs. The analysis revealed that in the six SSGs, players performed the most Acc and Dec, then COD Right and the least COD Left. From the third game on, a decrease in the number of COD Right was noticed. We hypothesized that progressive neuromuscular fatigue on the dominant side caused a more symmetrical trend in COD.